Analisis Pengalaman Pengguna pada Aplikasi Mobile Banking dengan Metode UX Curve (Studi Kasus : BRI Mobile Banking) - Nadiatul Khaira; Hanifah Muslimah Az-Zahra; Alfi Nur Rusydi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Bank BRI is one of the banks that have provided digital services for their customers. BRI management realizes that if they do not actively innovate, they will be displaced by banks that are more advanced in their technological development, given the current needs of the community. This study aims to identify changes in user experience by evaluating long-term user experience using the UX Curve method. In the data collection stage, the UX Curve is divided into 5 points of view, namely general UX, degree of use, utility, ease of use, and attractiveness and produce 100 curves. Based on the 100 curves obtained, the resulting improving curves amounted to 44 curves, the resulting deteriorating curves amounted to 39 curves and the resulting stable curves totaled 17 curves. The reasons for changing user experience on the BRI Mobile Banking application were as many as 514 reasons for changing the application with an average of 29.6 (14.55 positive and 11.15 negative N = 20). The reasons most frequently cited by respondents are reasons that fall into the usability aspect of 177 with an average of 8.85 (5.35 positive and 3.5 negative, N = 20). Meanwhile, the category with the least reason is the motivational category with an average of 2.1 (1.35 positive and 0.75 negatives, N = 20). Based on aspects of this reasoning it can be concluded that the aspect that most influences the change in the user experience of BRI Mobile Banking applications is the usability aspect.